Pengaruh Lingkungan Kerja Fisik Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Camat Penukal Kabupaten Pali - Iis Oktavia; Hamid Halin; Endah Dewi Purnamasari (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study aims to find out how the influence of the physical work environment and work motivation on employee performance at the Penukal sub-district office, Pali district. In this study, it was collected by distributing questionnaires to 42 respondents. The data analysis technique used is a multiple linear regression model by testing the classical assumptions. While those used to see the extent to which the accuracy and feasibility of research instruments (measuring variables) are used to test the validity and reliability. Hypothesis testing is done by t test and F test. The results of this study indicate that partially the physical work environment has a significant effect on employee performance (Sig.t 0.002 <0.05, H1 is accepted), and work motivation has a significant effect on employee performance at the Penukal District Office of Pali Regency (Sig.t 0.005 <0 .05, H2 accepted). The results of the F test analysis and the coefficient of determination show that simultaneously the physical work environment and work motivation have a significant effect of 42.2 percent on employee performance at the Penukal District Office of Pali Regency (Sig.F 0.000 <0.05, H3 is accepted). This shows that the better the physical work environment and the higher the work motivation that exists in employees, the better and higher the performance produced by TKS employees at the Penukal District Office, Pali Regency.